Regiones sub Polo Arctico - Blaeu, Willem Janszoon, 1571-1638 (1645)
Engraved double-page map, contemporary handcoloring; dampstain in lower right corner affecting image, small tear in lower margin entering printed frame. This is the second state of the map in 1645, which bears a decorative dedication to Guilielmo Backer. Blaeu's beautifully engraved map of the arctic was first issued c.1638 and is a precise copy of a map issued by Jansson the previous year. Burden notes "even the cartouches are the same. But Janssonius has placed his imprint in the lower right cartouche; Blaeu has the scale here." Along with the original Jansson, Blaeu's map "provides the first detailed summary of the 16th and early 17th century Canadian arctic discoveries" -- Kershaw. The map provides the best view of the period of discoveries in the area of Hudson's and Baffin's Bays as well as Davis Strait. It is a vast improvement over the Mercator map of the region, whose North Pole was filled with mythical islands. Frobisher' Strait is still mistakenly identified with Greenland, Frisland has disappeared. The curved rhumb lines present a new polar map feature that suggest compass directed routes. This Latin text edition was issued by Joan Blaeu in the 1662 or 1665 edition of the Atlas Maior. Burden, p. 252.